INVESTIGATION OF THE EFFECT OF THERMOMECHANICAL PROCESSING ON MICROSTRUCTURE AND CORROSION RESISTANCE OF 321 AUSTENITIC STAINLESS STEEL - M. Salehi (Isfahan University of Technology, 2021)
In this study, microstructural changes in the thermomechanical processing and its effect on the corrosion behavior of 321 austenitic stainless steel were investigated. EDS analysis and optical microscopy were used to identify precipitates and microstructure, respectively. To evaluate the corrosion properties, potentiodynamic polarization test and electrochemical impedance spectroscopy were performed. First, the as-received sample was subjected to cold rolling with a 90% thickness reduction at liquid nitrogen temperature, and then annealing was performed at temperatures of 750, 850, and 1050 °C for 10 min. The results showed that severe cold rolling slightly improved the corrosion properties and in annealed samples, the corrosion resistance increased with more uniform microstructure, more reversion of martensite phase to austenite, and reduction of grain size. Annealed samples at 850 °C and 1050 °C with polarization resistance values of 8.200 kΩ.cm2 and 3.800 kΩ.cm2 depicted the highest and lowest corrosion resistance compared to other samples, respectively.